Facilitating cross-cultural competence of students in an interactive VR learning environment - Rustam Shadiev, Xuan Chen, Wayan Sintawati, Fahriye Altinay, Yan Li, Nurassyl Kerimbayev, Ahmed Tlili (Educational Technology & Society)
Students are unable to view each other’s VR content created with 360-degree video technology using head-mounted displays and discuss it in real-time. This limitation may confine the application of 360-degree video technology in the field of intercultural learning to merely passive observation of cultural content on individual devices, thereby preventing simultaneous, interactive peer discussions about each other’s VR content, crucial for enriching intercultural learning experiences. Therefore, we aimed to address this issue in the present study by developing an interactive VR learning environment with such elements as (a) 360-degree video camera for creating cultural content, (b) 360-degree video viewing tool for viewing the created content, and (c) online video conference platform, enabling students to watch each other’s VR content and communicate about it simultaneously. We explored the feasibility of using such environment to facilitate cross-cultural competence development of students in a learning activity. To this end, we recruited 31 university students from China and Indonesia for this study. In this research, we explored whether the learning activity supported by technology can help to develop cross-cultural competence of the participants, types of interaction behavior among them, and the relationship between interactive behavior and cross-cultural competence. Finally, how the participants perceive the technology-supported cross-cultural learning activity was also investigated. The findings revealed that the activity was beneficial for the development of cross-cultural competence which was significantly improved. Guided by related research, the interactive behavior of students was categorized as cognitive, emotional, and social. Our results showed that only cognitive and emotional interactive behavior had relationship with student intercultural competence. Finally, the students positively perceived the activity because it was beneficial for cross-cultural learning. Our findings can be useful for educators and researchers in designing interactive learning activities in VR contexts, which have been found to impact students’ cross-cultural competence.